2012
DOI: 10.1002/ar.22503
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Tir Ubiquitylation Contributes to Enteropathogenic E. coli Remaining Extracellular During Nonphagocytic Cell Infections

Abstract: Enteropathogenic Escherichia coli (EPEC) is an extracellular pathogen that alters many host subcellular components during its infectious processes. We have previously shown that EPEC hijacks a large assortment of host cell endocytic components and uses these proteins to form protruding structures called ''pedestals'' rather than triggering internalization of the bacteria. Other invasive pathogens that also recruit similar endocytic components have been shown to enter their host cells on the ubiquitylation of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 80 publications
0
2
0
Order By: Relevance
“…Many pathogenic microorganisms have been identified for using the clathrin-mediated endocytic pathways to invade host cells. [72][73][74] A lipid raft-mediated endocytosis pathway was exploited by some pathogenic microorganisms, such as Chlamydia, for cell entry. Nishi K et al 50 reported that M. bovis can be internalized through a clathrin-dependent pathway or a clathrin-independent, lipid raft-mediated pathway, but the virulence factors responsible the mediated internalization process reunknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many pathogenic microorganisms have been identified for using the clathrin-mediated endocytic pathways to invade host cells. [72][73][74] A lipid raft-mediated endocytosis pathway was exploited by some pathogenic microorganisms, such as Chlamydia, for cell entry. Nishi K et al 50 reported that M. bovis can be internalized through a clathrin-dependent pathway or a clathrin-independent, lipid raft-mediated pathway, but the virulence factors responsible the mediated internalization process reunknown.…”
Section: Discussionmentioning
confidence: 99%
“…The colocalization of rLppB with clathrin and caveolin was found by confocal microscopy. Many pathogenic microorganisms have been identified for using the clathrin‐mediated endocytic pathways to invade host cells 72–74 . A lipid raft‐mediated endocytosis pathway was exploited by some pathogenic microorganisms, such as Chlamydia, for cell entry.…”
Section: Discussionmentioning
confidence: 99%